Progress in the application of reflectance confocal microscopy in dermatology - Lu, Quansheng; Jiang, Guan (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Reflectance confocal microscopy (RCM) is abbreviated as skin three-dimensional computed tomography, which can help clearly observe the structure of the epidermis and superficial dermis. It is a non-invasive skin disease examination method and provides fast access to real-time, dynamic skin micro-anatomical images. Therefore, RCM is widely used in the clinical diagnosis of skin diseases. For example, the RCM features of vitiligo are as follows: pigment loss or partial pigment loss in the lesion area, loss of the basal layer pigment ring. The RCM findings of Riehl melanosis are as follows: basal cell liquefaction and degeneration. The RCM results for verruca plana show: the Rose-like structure. The characteristics of psoriasis under RCM include: hyperkeratosis, parakeratosis, thickening of the spinous layer, capillary dilatation and hyperaemia, peripheral inflammatory cell infiltration. Epidermal brain-like structure was observed under RCM of seborrheic keratosis. With RCM, image acquisition and preservation of the skin is convenient, and the technique is convenient for comparing the development of lesions during long-term follow-up observation. Therefore, it helps to understand disease development in real time and dynamically and can be used to evaluate the curative effect. In this article, we briefly review the technical principles, diagnostic criteria for RCM application and RCM-related research progress in the diagnosis of pigmentary diseases, inflammatory diseases, skin tumours, and other common skin diseases.